PENGGUNAAN MEDIA PEMBELAJARAN KOTAK DAN KARTU MISTERIUS (KOKAMI) UNTUK MENINGKATKAN AKTIVITAS DAN KETUNTASAN BELAJAR SISWA PADA POKOK BAHASAN HIDROKARBON DAN MINYAK BUMI DI KELAS X.8 SMAN 9 PEKANBARU - Nasution, Wirda Novitasari; Haryati, Sri; ', Susilawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research is aimed to find out the improvement of the students’ learning activity and completeness by using mysterious card and box learning media in hydrocarbons and crude oil topic at X.8 grade of SMAN 9 Pekanbaru in academic year 2015/2016. This research is class action research with two cycles research design. The sample of this research was X.8 grade students. They were given a corrective action in learning process by using mysterious card and box learning media. The data were collected by giving test and observation method. The researcher analyzed the data descriptively by using percentage technique. Based on the result of the data analysis, it can be concluded that the use of mysterious card and box learning media can improve students’ learning activity and completeness in Hydrocarbons and crude oil topic at X.8 grade of SMAN 9 Pekanbaru. It can be seen by the improvement of students’ learning activity from 72.35% at the first cycle to 88.81% at the second cycle, and learning completeness from 89.47% at the first cycle to 100% at the second cycle.Keywords: Mysterious card and box learning media (KOKAMI), Learning Completeness